The effect of political communication on European financial markets during the sovereign debt crisis - Conrad, Christian; Zumbach, Klaus Ulrich (Journal of empirical finance, 2016)
We quantify all statements by major European politicians reported by Reuters during the August 2011 to December 2011 period and show that political communication significantly affects the EUR-USD exchange rate as well as European stock and bond markets. Communication with respect to Italy induces the strongest market reactions. Financial markets consider the German bond market a safe haven.
Gesehen am 04.05.2020